2002
DOI: 10.2298/vsp0202119m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nerve and fibroblast growth factors on the production of nitric oxide in experimental model of Huntington's disease

Abstract: The role of nitric oxide (NO) in neurological diseases represents one of the most studied, yet controversial subjects in physiology. The aim was to examine the effects of intrastriatal injection neurotrophins (nerve growth factors-NGF, fibroblast growth factors-FGF) in order to investigate the possible involvement of NO in quinolinic acid (QA) induced striatal toxicity in the rat model of Huntington's disease (HD). QA was administered unilaterally into the striatum of adult Wistar rats in a single dose of 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…FGF-2 is expressed in substantia nigra, striatum, and globus pallidus of human brain, and FGF receptor expression is increased in HD (36). In the quinolinic acid model of HD in rats, FGF-2 attenuates changes in cytochrome c oxidase (37) and nitric oxide synthase (24) activity, but there is little other prior evidence to connect FGF-2 with HD. The mechanisms through which FGF-2 produced neuroprotection in our HD transgenic R6͞2 mice may relate to the Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-2 is expressed in substantia nigra, striatum, and globus pallidus of human brain, and FGF receptor expression is increased in HD (36). In the quinolinic acid model of HD in rats, FGF-2 attenuates changes in cytochrome c oxidase (37) and nitric oxide synthase (24) activity, but there is little other prior evidence to connect FGF-2 with HD. The mechanisms through which FGF-2 produced neuroprotection in our HD transgenic R6͞2 mice may relate to the Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the administration of antioxidant molecules blocks, reverses and prevents deterioration and molecular changes in both chemically-induced and transgenic animal models [22,23]. Studies using experimental HD models have shown that treatment with NGF lowers nitrotyrosine levels, indicating that NGF exerts a neuroprotective effect on striatum neurons [24,25]. Additionally, Cao et al have highlighted the therapeutic potential of nerve growth factor, noting that NGF administration causes a reduction in oxidative damage and enhances the capacity for cell proliferation and ROS scavenging [26].…”
Section: Discussionmentioning
confidence: 99%